1. IMPROVING KNOWLEDGE AND PRACTICES ON LUMBAR SPINE PAIN PREVENTION AMONG PATIENTS AT THE REHABILITATION DEPARTMENT OF HCM HOSPITAL FOR TRAUMATOLOGY AND ORTHOPEDICS (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to assess the knowledge and preventive practices regarding lumbar spine pain among patients at the Rehabilitation Department of Ho Chi Minh City Hospital For Traumatology and Orthopedics. The study also evaluated the effectiveness of an educational intervention in improving patients' knowledge and altering their preventive practices.Methods: A cross-sectional descriptive study combined with a pre-post intervention was conducted on 140 patients suffering from lumbar spine pain. Data were collected through self-administered questionnaires evaluating the patients' knowledge and practices before and after the intervention. The results were analyzed using SPSS software.Results: After the intervention, the proportion of patients with correct knowledge about lumbar spine pain prevention increased from 35% to 60%, while the proportion of correct practices rose from 30% to 65%. The study also found a strong correlation between knowledge and practice, with patients possessing better knowledge tending to exhibit correct preventive behaviors.Conclusion: The educational intervention significantly improved the patients' knowledge and preventive practices regarding lumbar spine pain. The study suggests maintaining and expanding such educational programs to further enhance patient awareness and preventive practices in the future.
Keywords: lumbar spine pain; knowledge; practices; prevention; educational intervention